PASTORAL KONSELING PADA NY. X YANG DEPRESI AKIBAT HAMIL DILUAR NIKAH - Betrik Sipahutar (IAKN Tarutung, 2019)
Abstract - This Research aim to to know how to give the help through pastoral konseling to Ny X which pregnant depresi effect outside marrying. Research target and analyse to case in this article: 1). cause Konseli experience of the depresi because its husband leave she is as well as its family avoid. Pastoral Konseling done by a writer is for example comprehending x'self existence by doing approach konseling, 2). As for alternative which on the market to Ny.X is going abroad to return to other; dissimilar area so that able to answer the demand the its child requirement is everyday so that do not become the burden for its parent and do not become the discussion substance for vinicity people. Alternative which on the market konselornya to Ny X accepted by konseli better, because konseli think have she ought to go abroad to answer the demand its requirement is everyday Words Lock The: Pastoral Konseling, Depresi, To Ny X.